Volcanic ash layers illuminate the resilience of Neanderthals and early modern humans to natural hazards - Lowe, J; Barton, N; Blockley, S; Ramsey, C; Cullen, V; Davies, W; Gamble, C; Grant, K; Hardiman, M; Housley, R; Lane, C; Lee, S; et al. (National Academy of Sciences, 2012)
Marked changes in human dispersal and development during the Middle to Upper Paleolithic transition have been attributed to massive volcanic eruption and/or severe climatic deterioration. We test this concept using records of volcanic ash layers of the Campanian Ignimbrite eruption dated to ca. 40,000 y ago (40 ka B.P.). The distribution of the Campanian Ignimbrite has been enhanced by the discovery of cryptotephra deposits (volcanic ash layers that are not visible to the naked eye) in archaeological cave sequences. They enable us to synchronize archaeological and paleoclimatic records through the period of transition from Neanderthal to the earliest anatomically modern human populations in Europe. Our results confirm that the combined effects of a major volcanic eruption and severe climatic cooling failed to have lasting impacts on Neanderthals or early modern humans in Europe. We infer that modern humans proved a greater competitive threat to indigenous populations than natural disasters.